Online social support and problematic Internet Use—a meta-analysis - Ma, Yujun; Zhou, Ziyao; Ye, Chenxi; Liu, Mengxin (Addictive behaviors, 2025)
•This meta-analysis examines the relationship between online social support (OSS) and problematic Internet use (PIU).•OSS is moderately and significantly correlated with PIU.•The relationship was more pronounced in studies with a higher proportion of female participants.•When PIU was measured by problematic social media use, the relationship with OSS was stronger than in studies that measured PIU by general problematic Internet use or problematic mobile phone use. The internet is a crucial platform for individuals to gain social support, enhancing their well-being. However, research indicated that while online social support (OSS) has positive aspects, it also carries potential drawbacks and can lead to problematic Internet use (PIU). This study aims to examine the complex relationship between OSS and PIU. Adhering to the PRISMA guidelines, a systematic literature search was performed across five English and three Chinese databases. A total of 1966 articles were initially screened by title, followed by abstract, and finally, full text. And the random-effects model was used to synthesize the included 31 studies. 31 studies were identified, encompassing a total sample of 22,375 participants. Meta-analysis revealed a moderate and significant correlation between OSS and PIU (r = 0.293), and it was significantly moderated by gender and the measurement methods of PIU. Notably, the relationship was more pronounced in studies with a higher proportion of female participants; when PIU was measured by problematic social media use, the relationship with OSS was stronger than studies that measured PIU by general problematic Internet use or problematic mobile phone use. These findings contribute to a comprehensive understanding of the association between OSS and PIU, and carry implications for identifying and addressing the potential risks associated with social support provision in the digital realm.